Parents as Teachers: The Influence of Internal and External Factors on Parenting Style Differences - Rose Mini Agoes Salim; Shahnaz Safitri (Universitas Negeri Surabaya, 2020)
Research on the relationship between parents and children consistently shows that parents play a major role in developing the child's personality and skills. The influence of parents on children, among others, took place through parenting style. In the Indonesian context, teachers had also been viewed as an authority whose role was similar to parents in educating children, considering students spent a remarkable amount of time learning together with teachers at school. Based on this reason, this study explored whether the parenting styles adopted by teachers as parents at their homes were related to the parenting styles they applied to students at school. We also examined the extent to which gender and education levels influenced parenting. Using accidental sampling, this study was conducted on 501 teachers from five cities in Indonesia using the Parenting Style Scale. The analysis showed that there was a positive relationship between the teacher's parenting styles at home and school. Furthermore, gender was a significant factor in distinguishing one dimension of parenting style, in contrast to the level of education. Further analysis found that domicile influenced parenting behavior, which indicated the role of culture in parenting practices.Abstrak: Riset terkait hubungan orangtua dan anak secara konsisten menunjukkan bahwa orangtua berperan besar dalam mengembangkan kepribadian dan keterampilan anak. Pengaruh orangtua terhadap anak antara lain berlangsung melalui pola asuh yang diterapkan. Pada konteks Indonesia, guru juga dipandang sebagai pihak otoritas layaknya orangtua untuk mendidik anak, khususnya mengingat siswa menghabiskan waktu yang cukup lama untuk belajar bersama dengan guru di sekolah. Untuk itu, penelitian ini menelusuri apakah pola pengasuhan yang diadopsi oleh guru sebagai orangtua berkaitan dengan pola pengasuhan yang diterapkan pada siswa di sekolah. Lebih lanjut, ditelusuri pula seberapa jauh atribut demografi berupa gender dan tingkat pendidikan mempengaruhi pola asuh. Menggunakan teknik aksidental sampling, penelitian ini dilakukan pada 501 guru dari lima kota di Indonesia menggunakan Skala Pola Asuh dalam bentuk kuesioner cetak. Hasil analisis menunjukkan terdapat hubungan positif antara gaya pengasuhan guru di rumah dan di sekolah. Lebih lanjut, gender menjadi faktor yang signifikan membedakan pola asuh pada salah satu dimensi pengasuhan, sementara tidak demikian dengan tingkat pendidikan. Analisis lanjutan juga menemukan bahwa tempat tinggal memengaruhi perilaku pengasuhan, yang mengindikasikan peran budaya di dalam praktik pengasuhan.Kata kunci: Gaya pengasuhan, guru, keluarga